2019
DOI: 10.2196/13560
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Web-Based Monitoring System for Power Tilt-in-Space Wheelchairs: Formative Evaluation

Abstract: BackgroundIn order to prevent pressure ulcers, wheelchair users are advised to regularly change position to redistribute or eliminate pressure between the buttocks region and the seat of the wheelchair. A power tilt-in-space wheelchair (allowing simultaneous pivoting of the seat and the backrest of the wheelchair toward the back or front) meets many clinical purposes, including pressure management, increased postural control, and pain management. However, there is a significant gap between the use of tilt as r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
(55 reference statements)
0
4
0
5
Order By: Relevance
“…The sensor-based monitoring system collects data on the use of power wheelchairs, specifically tracking tilt angle and time spent in the wheelchair (time seated and time tilted). If pre-determined behavior targets are not met, a sound or vibration notification is issued to the AT user as a reminder [ 21 ]. The sensor-based monitoring system is also connected to the clinicians’ intervention system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensor-based monitoring system collects data on the use of power wheelchairs, specifically tracking tilt angle and time spent in the wheelchair (time seated and time tilted). If pre-determined behavior targets are not met, a sound or vibration notification is issued to the AT user as a reminder [ 21 ]. The sensor-based monitoring system is also connected to the clinicians’ intervention system.…”
Section: Resultsmentioning
confidence: 99%
“…While our initial work embraced AT for various limitations (mobility, vision, communication, …), through the intervention mapping approach we refined the target population to users of mobility aids only: manual and power wheelchairs, wheeled bases, scooters, rollator walkers, walkers and quadripod canes. As such, the Internet-based intervention aimed to address abovementioned gaps by providing non-emergency remote monitoring, support, and training resources to facilitate behavior change in older adult AT users and their caregivers, and to mitigate negative outcomes that can be associated with mobility AT use [ 18 , 19 , 20 , 21 ]. With MOvIT+™, remote monitoring is done via self-report questionnaires completed by the AT user or caregiver through customized data collection methods (online, SMS or interactive voice-response system), clinician report (clinical portal) and internet of things (sensors attached to a device post-delivery).…”
Section: Introductionmentioning
confidence: 99%
“…The objective is to test the teledance intervention, including a series of video vignettes adapted for stroke rehabilitation and follow-up modalities with users (asynchronous and synchronous). To do so, the intervention will be subject to a formative evaluation by the users to identify and resolve problems that may influence their experience [ 61 ] and to explore its potential impacts. By testing the intervention within an intensive functional rehabilitation setting, the objective is to identify the characteristics of users to whom such an intervention can be applied, evaluate its usability and safety, and explore its potential impacts.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we will use the 'think aloud' method [48], in which patients and care providers can speak aloud any words in their mind as they read through parts of the intervention plan. The think-aloud research method has been demonstrated to provide valid data on participant thinking and was successfully used in other intervention development studies [49,50]. Based on the results obtained, further modifications will be made, resulting in a pre-tested version of the intervention plan ready for implementation in practice.…”
Section: Designmentioning
confidence: 99%